Analisis Pengaruh Strategi Penempatan Lokasi Pedagang Kaki Lima terhadap Tingkat Omset Penjualan di Area USU (Pintu 1 - Pintu 4) - Nainggolan, Sonia Cleophani; Rossevelt, Franklin Asido; Aisyah, Dara; Simanullang, Oktavia Immanuella; Putri, Siti Aisyah Riani; Hasibuan, Cindy Triana; Hafizh, Harits Tio (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The informal sector, particularly street vendors, plays a strategic role in urban economies by providing employment opportunities and affordable goods and services. One of the key determinants of street vendors’ economic performance is business location strategy. This study aims to analyze the effect of location placement strategy on the sales turnover of street vendors in the Universitas Sumatera Utara (USU) area, specifically at Gate 1 to Gate 4. This study employs a quantitative approach using a survey method. Data were collected through a five-point Likert-scale questionnaire measuring location strategy dimensions—accessibility, visibility, proximity to pedestrian flows, vendor clustering, and supporting facilities—as well as sales turnover. Data analysis was conducted using validity and reliability tests, Pearson correlation, and multiple linear regression with SPSS software. The results indicate that all research instruments are valid and reliable. Simultaneously, location placement strategy has a positive and significant effect on sales turnover. Partially, all location dimensions significantly influence sales turnover, with supporting facilities and spatial arrangement emerging as the most dominant factor. These findings highlight the critical role of spatial and environmental factors in enhancing the economic performance of street vendors in campus areas.